Ephedraphis Hille Ris Lambers (Hemiptera: Aphididae), with a key to species and one new species from Mongolia - Zhang, Bin; Qiao, Gexia (Zootaxa, 2013)
The aphid genus Ephedraphis Hille Ris Lambers is reviewed. The genus is represented by four species, including Ephe-draphis mongolica sp. n. on Ephedra sp. from Umnogovi Province, Mongolia. A key to the known species of Ephedraphis is provided. Diagnostic characters of all species are given. All specimens studied, including type specimens are deposited in the National Zoological Museum of China, Institute of Zoology, Chinese Academy of Sciences, Beijing, China.